1986
DOI: 10.1037/0033-295x.93.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Under what conditions does theory obstruct research progress?

Abstract: Researchers display confirmation bias when they persevere by revising procedures until obtaining a theory-predicted result. This strategy produces findings that are overgeneralized in avoidable ways, and this in turn hinders successful applications. (The 40-year history of an attitude-change phenomenon, the sleeper effect, stands as a case in point.) Confirmation bias is an expectable product of theorycentered research strategies, including both the puzzle-solving activity of T. S. Kuhn's "normal science" and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
286
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(291 citation statements)
references
References 104 publications
(128 reference statements)
2
286
0
3
Order By: Relevance
“…The use of competing hypotheses reduces the risk of confirmation bias. 10,11 The first two hypotheses concern the 'quality' of the perceptions held of the brand, while the third hypothesis focuses on the quantity of perceptions devoted to the brand.…”
Section: Brand Image and Customer Loyaltymentioning
confidence: 99%
“…The use of competing hypotheses reduces the risk of confirmation bias. 10,11 The first two hypotheses concern the 'quality' of the perceptions held of the brand, while the third hypothesis focuses on the quantity of perceptions devoted to the brand.…”
Section: Brand Image and Customer Loyaltymentioning
confidence: 99%
“…However, later they proposed that message recipients may not entirely forget the cue, yet the association between the representations of the discounting cue and the message content may fade over time and produce a sleeper effect (Hovland & Weiss, 1951). These two formulations differ in that (a) forgetting implies that the traces of the cue disappear or become unavailable in memory over time, whereas (b) dissociation implies that the cue remains available in memory but is simply less easily retrieved (less accessible) in relation to the topic of the communication.Decades later, Greenwald, Pratkanis, and colleagues argued that the impact of the message and the cue decay at different rates (Greenwald, Pratkanis, Leippe, & Baumgardner, 1986;Pratkanis et al, 1988). This hypothesis encompasses the possibility that the discounting cue can become either unavailable or inaccessible as time elapses.…”
mentioning
confidence: 99%
“…This reasoning, termed confirmation bias, is strongly supported by studies which show that people tend to seek out evidence that confirms their current position and to disregard evidence that conflicts with their current position (Einhorn and Hogarth 1978). In fact, several studies have specifically shown that preliminary hypotheses based on early, relatively impoverished data interfere with the later interpretations of better, more abundant data (Greenwald, Pratkanis et al 1986;Reason 1990). The tendency to disregard conflicting evidence as a corollary to the confirmation bias is pervasive (Anderson and Jacobson 1965;Slovic 1966).…”
Section: (22% Of Respondents Picked This Option)mentioning
confidence: 99%